Herbs and athletes - Kundrat, S. (Sports Science Exchange, 2005)
This article will review what little research published in English is available on several herbs that athletes may use in hopes of improving health and/or performance. Sports-related uses include enhancing performance in prolonged endurance events, inducing muscular hypertrophy and increasing strength, decreasing body fat, speeding recovery, and improving performance in team sports (Bucci, 2000). Many athletes may use herbal products to try to aid in healing after an injury, to decrease inflammation, to manage pain, to stay more alert, and to boost immunity and optimize their chances of staying healthy in and out of season, enabling them to compete at the highest level possible. There is insufficient research on the use of herbs by athletes to make firm recommendations, and that is not the intent of this article. Rather, this brief review provides an introduction to what little science on selected herbs is available in the English literature. Moreover, it is important to remember that some of the phytochemicals in herbs may have harmful side effects, including adverse interactions with medicines the athlete may be taking. In short, athletes should be extremely wary about ingesting herbs containing unknown amounts of unknown chemicals for unclear benefits with the possibility of harmful side effects.